Relationship between the need for orthodontic treatment and DMFT index in adults - Clarisse Virginia Díaz-Reissner; Juan Roldán-Merino; Irma Casas-García (Universidad de Antioquia, 2022)
Introduction: it has been found that subjects with higher DMFT index scores were more likely to require orthodontic treatment. The objective was relationship the need for orthodontic treatment and DMFT index in a population of Paraguayan adults in 2017. Methods: cross-sectional study in adult patients ≥18 years of age who attended the dental clinic of the Facultad de Odontología (Faculty of Dentistry) of the Universidad Nacional de Asunción (National University of Asunción) during the Supervised Internship in January and February 2017. The Dental Aesthetic Index (DAI), was used for the need for orthodontic treatment. Pearson's Chi-square and ANOVA statistical tests were used along with the Bonferroni test at the 95% level. Results: 147 adults were part of the study, where 71.4% were women. The DAI was 31.1 ± 10.3. Found, 29.5% required priority orthodontic treatment. And 65.3% presented increased incisal overhang, 55.1% crowding and 51.7% abnormal molar ratio. The DMFT Index was 8.9 ± 5.9. As the CPO-D index increases, the level of need for orthodontic treatment also increases (p<0.001), being the difference statistically significant between the none and priority levels (p <0.001). Conclusions: the DMFT index was found to be significantly associated with the level of need for orthodontic treatment.